Continuous Theta-Burst Stimulation Over the Right Orbitofrontal Cortex in Treatment-Resistant Obsessive-Compulsive Disorder Treatment: A Randomized Sham-Controlled Trial - Liu W; Shao H; Liao J; Yang D; Ma M; Yang J (International Journal of General Medicine, 2021)
Weiwei Liu,1,* Hua Shao,2,* Jing Liao,1 Dalu Yang,1 Maoliang Ma,3 Jianli Yang2 1Tianjin Medical University, Tianjin, People’s Republic of China; 2Clinical Psychology Department, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China; 3Tianjin Medical University General Hospital Airport Site, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianli YangClinical Psychology Department, Tianjin Medical University General Hospital, Anshan Road #154, Heping District, Tianjin, People’s Republic of ChinaEmail adyy005@163.comPurpose: Examining whether modulation of right orbitofrontal cortex (OFC) activity by continuous theta-burst stimulation (cTBS) affects obsessive-compulsive disorder (OCD) symptoms.Patients and Methods: A total of 28 treatment-resistant OCD participants were treated with either active or sham cTBS of the OFC twice per day, for five days a week, for 2 weeks, in a double-blinded manner. Clinical response to treatment was determined using the Yale–Brown Obsessive-Compulsive Scale (Y-BOCS).Results: There were no statistically significant differences between the 2 groups after two weeks of treatment in the Yale–Brown Obsessive-Compulsive Scale score (group*time interaction, F2,20=0.996, p=0.387) and other secondary outcome measures, including anxiety symptoms and responder rates. Depressive symptoms improved significantly in the active group (p=0.027), but the significant difference disappeared at 6 weeks (p=0.089).Conclusion: This is the first randomized controlled study using cTBS in the right OFC to observe the improvement of treatment-resistant OCD symptoms. It is safe to use cTBS, but 2 weeks of treatment is not enough to achieve a curative effect. Future studies are needed to explore more advanced stimulation parameters suitable for the treatment of OCD.Clinical Trial Registration: www.chictr.org.cn, identifier ChiCTR2000034814.Keywords: obsessive-compulsive disorder, continuous theta-burst stimulation, orbitofrontal cortex, transcranial magnetic stimulation